Emma Russell: capstone - Russell, Emma, artist (Colorado State University. Libraries, 2021)
The artist's statement: I create for the sake of communication. All forms of art are a conversation between the creator and viewer. To me, graphic design is all about considering the viewer and how to best communicate a message about an idea, brand, or product through imagery. On top of that, it is about catching the eye and initiating a want to act. What I love about graphic design is the back and forth between the client, the viewers, and the creator. The communication that flows through each step of the creative process. As I work, I consider the ways people may view the artwork, whether they are the client or consumer. The foundation of the creative process is the research and investigative questions to find what a client wants. I aim to learn all that I can about the brand, product, message being represented because my job as a designer is to first characterize and define the project to then form an aesthetic. The rest is sketching, some more communication, and finally bringing the idea to life. In my personal work, I find myself drawn to media. The way that we function through technology today has sculpted our relationships, our expectations, and even our lifestyles and careers. A person can make a living solely by posting pictures and videos on social media. Our relationships function around social media and we expect each other to follow, continuously like, and share. We continue and strengthen our connections through our technology, it is the only "how" we know. As humans who naturally communicate on our own, we seem so reliant on this tool to form or maintain relationships. That interests me, as my profession is engrained within technology and media. My interests assist me in better creating for the sake of catching the eye because in the overcrowded digital marketing world we need to work harder to attract and bring people in. The instant nature of social media has impacted the way I approach each project, as well as showing the importance of making imagery easy to read, engaging, and include a call to action.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design